Valoración del estado nutricional y su relación con los hábitos alimenticios en los niños de 5 a 11 años de la escuela del barrio Kurintza, cantón Yacuambi. año 2015 - Chalán Ortega, Marcia Fabiola (2016)
The purpose of this research was to determine the nutritional status and its relationship with eating habits in children 5 to 11 years of school Kurintza, Yacuambi Canton neighborhood. 2015. For this purpose the survey and observation with survey instruments and observation guide applied to children and mothers, was used as technical design was cross-sectional, descriptive, bibliographic and field fixed rate. The results were; predominates the age group 10 to 11 years with 43.75%, males with 55%, the Shuar ethnic group with 95%, 34% of children and 21% of girls are underweight. Risk factors are affecting the low level of knowledge of mothers about nutrition with 81.58%, lower socioeconomic familiar with 92.11%, 60.53% the engaged in agriculture, receive 100% collation school every day, 40% have introduced diseases in the last 6 months, 71.25% received medical care, children with weight below the 95.45% of children did not receive exclusive breastfeeding; 90.91% do not consume dairy products, meat consume 93.18% less than 3 times a week, 81.82% and 63.64% do not consume vegetables or legumes, respectively, 45.45% consume cereals daily, 77, 78% consumed fruit less than 3 times per week, 63.64% consume carbohydrates daily. An educational plan aimed at mothers and children about healthy eating and hygiene developed. It is concluded that the highest percentage of children are underweight with 55% being the problems the lack of adequate nutrition for age as a factor incident. Keywords: Rating, nutritional status, eating habits, Children 5 to 11 years.